POLÍTICA HABITACIONAL E LOCAÇÃO SOCIAL EM SALVADOR - Baltrusis, Nelson; Nazem Mourad, Laila (Caderno CRH, 2014)
Este artigo tem como objetivo analisar o mercado imobiliário de locação em Salvador. Num primeiro momento, caracterizaremos o problema habitacional em Salvador, para o que nos apoiaremos nas diretrizes e ações previstas no Plano Municipal de Habitação de Interesse Social (PMHIS). Em seguida, trataremos das políticas implantadas pelos governos do estado e federal, destacando a experiência do Programa de Arrendamento Residencial (PAR) e incorporando algumas considerações sobre o Programa Minha Casa, Minha Vida. Também será abordada a questão do mercado de locação em Salvador a partir do perfil de moradores e da dinâmica do mercado. PALAVRAS-CHAVE: Aluguel social. Política de habitação. Instrumentos de planeamento urbano. HOUSING POLICY AND SOCIAL RENT IN SALVADOR, BRAZIL Nelson Baltrusis Laila Nazem Mourad This article seeks to analyze the real state rental market in Salvador, Brazil. Initially, we describe the housing problem in Salvador based on the guidelines and actions foreseen in the Municipal Plan for Social Interest Housing (PMHIS). Then we treat the policies implemented by state and federal administrations, emphasizing the experience of Social Leasehold Housing (PAR), and including a few considerations on My Home, My Life program. We also approach the issue of the rental market in Salvador based on the profile of dwellers and on the dynamics of the market. KEYWORDS: Social rent. Housing policy. Urban planning instruments. POLITIQUE DE L’HABITAT ET LOGEMENTS SOCIAUX À SALVADOR Nelson Baltrusis Laila Nazem Mourad L’objectif de cet article est d’analyser le marché de l’immobilier destiné à la location à Salvador. Dans un premier temps, et pour caractériser le problème du logement à Salvador, nous nous basons sur les directives et les actions prévues par le Plan Municipal des Logements Sociaux (PMHIS). Nous abordons ensuite les politiques mises en place par le gouvernement fédéral, mettons en évidence l’expérience du Programme de Bail Résidentiel (PAR) et nous y ajoutons quelques considérations concernant le Programme “Ma Maison, Ma Vie”. La question du marché locatif à Salvador est également traitée à partir du profil des habitants et de la dynamique du marché. MOTS-CLÉS: Location sociale. Politique de l’Habitat. Instruments de planification urbaine. <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH no Scielo: http://www.scielo.br/ccrh<span style="color: #000000; font-family: Verdana,Arial,Helvetica; font-size: 12px; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff; display: inline ! important; float: none;"> <small style="color: #000000; font-family: Verdana,Arial,Helvetica; font-style: normal; font-variant: normal; letter-spacing: normal; line-height: normal; text-indent: 0px; text-transform: none; white-space: normal; word-spacing: 0px; background-color: #ffffff;">Publicação Online do Caderno CRH: http://www.cadernocrh.ufba.br